The Clinical Application of Robot-Assisted Ventriculoperitoneal Shunting in the Treatment of Hydrocephalus - Liu, De-feng; Liu, Huan-guang; Zhang, Kai; Meng, Fan-gang; Yang, An-chao; Zhang, Jian-guo (Frontiers in Neuroscience, 2021)
Background This work aims to assess the effectiveness and safety of robotic assistance in ventriculoperitoneal shunting and to compare the results with data from traditional surgery. Methods We retrospectively analyzed 60 patients who had undergone ventriculoperitoneal shunting, of which shunts were implanted using a robot in 20 patients and using traditional surgical methods in the other 40 patients. Data related to surgery were compared between the two groups and the accuracy of the drainage tube in the robot-assisted group was assessed. Results On comparing the two groups, operation duration, intraoperative blood loss, the success rate of a single puncture, surgery-related complications, contact choroid plexus, and bone hole diameter were all found to be statistically different (P<0.05). There was no significant difference in the hospitalization time. In the robot-assisted surgery group, the average radial error was 2.4±1.5 mm and the average axial error was 1.9±2.1 mm. Conclusion In summary, robot-assisted implantation is accurate, simple to operate, practical, the duration of surgery is short, trauma to the patient is reduced, and fewer postoperative complications relating to surgery are reported.